Administration of oral and vaginal prebiotic lactoferrin for a woman with a refractory vaginitis recurring preterm delivery: Appearance of lactobacillus in vaginal flora followed by term delivery. Issue 2 (7th October 2013) - Otsuki, Katsufumi; Tokunaka, Mayumi; Oba, Tomohiro; Nakamura, Masamitsu; Shirato, Nahoko; Okai, Takashi
Abstract Lactoferrin (LF) is one of the prebiotics present in the human body. A 38‐year‐old multiparous woman with poor obstetrical histories, three consecutive preterm premature rupture of membrane at the 19th, 23rd and 25th week of pregnancy, was referred to our hospital. She was diagnosed as having refractory vaginitis. Although estriol vaginal tablets were used for 4 months, the vaginitis was not cured. We administrated vaginal tablets and oral agents of prebiotic LF, resulting in a Lactobacillus predominant vaginal flora. When she was pregnant, she continued to use the LF, and the Lactobacillus in the vaginal flora was continuously observed during pregnancy. An elective cesarean section was performed at the 38th week of pregnancy. When the administration of LF was discontinued after the delivery, Lactobacillus in the vaginal flora was disappeared.